Semiotics of Peasants in Transition : Slovene Villagers and Their Ethnic Relatives in America - Portis-Winner, Irene, 1923- (Book collections on Project MUSE., 2002)
Offers a new way of doing ethnography, based on an analysis of interaction between immigrants from a small village in Slovenia to the U.S. and the culture they left.